Innovation capabilities and their effect on innovative performance in food and beverage companies in La Cruz, Elota, Sinaloa - Bastidas Regalado, Viridiana; Alcázar Guzmán, Arely; Hi Rivera, Abraham (Acta Universitaria, 2026)
Despite innovation efforts in Sinaloa, research and development (R&D) data, as a percentage of gross domestic product (GDP), accounts for less than 0.3% of this expenditure. Therefore, this research analyzes the innovation capabilities and their impact on the innovative performance of food and beverage companies in the city of La Cruz, Elota, Sinaloa. Regarding the methodology, structural equations using the partial least squares method (PLS-SEM) were used to analyze data from a sample of 57 organizations. Results show a positive impact of innovation capabilities on companies’ innovative performance, which is useful for organizations and public policymakers when designing their innovation strategies or considering the capabilities they wish to improve for the development of the tourism sector.